Attention of Economic Growth and Oil Prices: Evidence from Indonesia - Syaharuddin, Yijo; Purwadi, Purwadi; Sampeliling, Alexander (International Journal of Energy Economics and Policy, 2021)
Oil is a commodity that can cause turmoil for the global economy. This study attempts to examine the relationship between oil prices and economic growth together with the exchange rate and inflation rate in Indonesia. The time span covered by this series is from 2000 (Q1) to 2019 (Q4), providing 80 observations. Tests carried out in this study included unit root testing through Augmented Dickey-Fuller (ADF) testing, Phillips-Perron (PP) testing, Kwiatkowski-Phillips-Schmidt-Shin (KPSS) testing, Johansen and Juselius cointegration test, Granger-based causality test. Vector Error Correction Model (VECM) to determine long-term and short-term relationships, and Variance Decomposition and Impulse Response Function to investigate relationships outside the sample. The empirical findings show that there is a relationship between variables, oil prices not only affect economic growth but also have an impact on the exchange rate and inflation rate. Furthermore, the results of the short-run Granger causality for the tested variables indicate a unidirectional causality that runs from all independent variables, namely oil prices, exchange rates, and the rate of inflation on GDP. In addition, there is a causal relationship between GDP and other determinants outside the sample. The addition of time-frames and variables can add to the variance of the sustainability of these findings in the future. Keywords: Oil price shocks, Economic growth, Panel data, Regression method, Indonesia. JEL Classification: D24, A1, C23 DOI: https://doi.org/10.32479/ijeep.11538